2016
DOI: 10.1016/j.vaccine.2016.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Parental experiences with vaccine information statements: Implications for timing, delivery, and parent-provider immunization communication

Abstract: Objective We examined Vaccine Information Statements (VIS) dissemination practices and parental use and perceptions. Methods We conducted a national online panel survey of 2603 US parents of children aged <7. Primary outcomes included reported VIS receipt, delivery timing, reading experiences, and perceived utility. Results Most parents received a VIS (77.2%; [95% CI: 74.5–79.7%]), 59.7% [56.6–62.7%] before vaccination but 14.5% [12.5–16.8%] reported receiving it after their child’s immunization; 15.1% [13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…However, prior research has identified early vaccine delay and/or refusal that may leave young children susceptible to infectious diseases [4,5]. Recent findings indicate variability in parental attitudes may link to their confidence in vaccines, perceived immunization need, social norms, and message influences [69]. Although national childhood vaccination coverage remains at a level sufficient to mitigate sustained large-scale outbreaks, decreases in confidence in vaccination may lead to drops in childhood immunization rates that could threaten the herd immunity built up by public health efforts over the last few decades [1014].…”
Section: Introductionmentioning
confidence: 99%
“…However, prior research has identified early vaccine delay and/or refusal that may leave young children susceptible to infectious diseases [4,5]. Recent findings indicate variability in parental attitudes may link to their confidence in vaccines, perceived immunization need, social norms, and message influences [69]. Although national childhood vaccination coverage remains at a level sufficient to mitigate sustained large-scale outbreaks, decreases in confidence in vaccination may lead to drops in childhood immunization rates that could threaten the herd immunity built up by public health efforts over the last few decades [1014].…”
Section: Introductionmentioning
confidence: 99%
“…10 Second, children delivered at hospitals were more likely to complete the HAV-I series. It was possible that mothers who delivered their babies at health facilities would use the health services more frequently, 11 including the childhood vaccination service. The administration of the 1 st dose of hepatitis B vaccine at birth in the obstetric hospitals might partly account for a better timeliness of the subsequent vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…Parent education may be in the form of conversations with a healthcare provider, 35,38,51,58 posters and other informational "advertisements" in waiting or exam rooms, 43,52,53,65 or more traditional educational materials such as Vaccine Information Sheets, brochures, or webpages. [31][32][33]51,58,[65][66][67] An RCT testing the combination of an educational video and information handout resulted in a statistically significant score reduction of 5.2 points on PACV (Parent Attitudes about Childhood Vaccines) 68 survey scores, indicating a reduction in parental vaccine hesitancy. 69 PACV is scored on a scale of 0 to 100, with 100 indicating high vaccine hesitance and lower scores representing less vaccine hesitance.…”
Section: Interventions For Parentsmentioning
confidence: 99%